An Inquiry to Globalization and Cultural Identity: A Search for Conceptual Framework - Lukas Maserona Sarungu (Insignia: Journal of International Relations, 2021)
The interaction between globalization and cultural identity is indeed quite problematic, and this is beyond doubt. The interactions' results do not seem to be counted accurately, and the results can be good or bad. Globalization should be seen as a double-edged knife, providing convenience and possibly eliminating some considered incompatible things with development. Cultural identities may be increasingly eroded by globalization. Still, they can also survive and develop in accordance with the existing conditions. For this reason, a conceptual framework is needed, so that it can explain these interactions. This paper will take the form of a literature review involving several journals and scientific literature. Through this literature review, an integrated theoretical framework is built that can be used to understand the concept of globalization and cultural identity. The method used in this paper is a systematic literature review. The resulting conceptual framework involves the role of the media and the state in continuing the ideas from the concept of globalization. The media will be able to form a symbol in society, and this symbol will become a common understanding for the community. Besides, globalization will facilitate the spread of the formation of this symbolization. Meanwhile, the state can encourage the construction of cultural identities that will also develop in society. The two concepts will be mutually sustainable in people's lives. Thus, it can be concluded that the state and the media have a significant share in the development of the cultural identity of local communities, which is formed from the phenomenon of globalization itself. Keywords: cultural identity, globalization, media, mass media, state